2005
DOI: 10.1002/jms.913
|View full text |Cite
|
Sign up to set email alerts
|

The role of different phenomena in surface‐activated chemical ionization (SACI) performance

Abstract: In previous studies, the production of ions in an APCI source without any corona discharge was observed, and the intensity of the ion signals showed significant increases on placing a metallic surface at 45 degrees inside an orthogonal ion source. This method was named surface-activated chemical ionization (SACI). The present study was performed to investigate the mechanisms of ion production with or without the presence of the metallic surface, by varying instrumental parameters and the geometrical configurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
60
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(60 citation statements)
references
References 15 publications
0
60
0
Order By: Relevance
“…Considering that the source employed for the present investigation has a 'linear' configuration (in other words the vaporizer and the entrance capillary are on the same axis), a metallic surface (stainless steel) was placed close to the vaporizing device with a small angle with respect to the vaporizer axis. In this condition the ion production is the results of two different phenomena: 7 (i) vaporization of the ions already present in solution and their better focalization with respect to the entrance capillary of the MS analyzer; (ii) ionization phenomena occurring on the surface. Relevant to this Letter to the Editor 711 approach are some instrumental parameters, among which the surface area, the nebulized solution flow and the voltage applied on the surface are the most important ones.…”
mentioning
confidence: 99%
“…Considering that the source employed for the present investigation has a 'linear' configuration (in other words the vaporizer and the entrance capillary are on the same axis), a metallic surface (stainless steel) was placed close to the vaporizing device with a small angle with respect to the vaporizer axis. In this condition the ion production is the results of two different phenomena: 7 (i) vaporization of the ions already present in solution and their better focalization with respect to the entrance capillary of the MS analyzer; (ii) ionization phenomena occurring on the surface. Relevant to this Letter to the Editor 711 approach are some instrumental parameters, among which the surface area, the nebulized solution flow and the voltage applied on the surface are the most important ones.…”
mentioning
confidence: 99%
“…However, the formation of abundant [M þ H] þ ions without the presence of a corona discharge has also been observed for molecules that are much less likely to have been significantly preionized in solution, (e.g., steroids.) (Cristoni et al, 2005a). The results indicate that, at least partially, the ionization takes place in the regions shown in Figure 2a.…”
Section: A Theoretical Ionization Mechanismmentioning
confidence: 77%
“…The sample is vaporized through the apparatus (1), it interacts with the charged surface (2) by the action of the desolvating nitrogen stream provided through the apparatus (1) and the ions formed by the surface activation effect are focalized to the high vacum region of the mass spectrometer through the mass spectrometer entrance hole (3). Cristoni et al (2005a) have recently shown the possible ionization mechanism of SACI. The authors have tried to understand and shown the real role of the surface.…”
Section: Surface-activated Chemical Ionizationmentioning
confidence: 99%
“…The higher signal intensity in SACI could be due to a higher analyte ionization efficiency and lower solvent ionization. [7] Thus, both LC-CEC-ESI-MS/MS and LC-CEC-SACI-MS/MS approaches were also tested to verify whether benefits, in terms of sensitivity, were achieved as compared with RP chromatography. The mass chromatograms obtained by injecting 5 µl of a 10 ng/ml enterotoxin A trypsin-digested fragment, SELQGTALGNLK, using both ESI and SACI are shown in Fig.…”
Section: Lc-rp-esi-ms/ms and Lc-rp-saci-ms/msmentioning
confidence: 99%
“…This increased sensitivity is probably due to the higher ionization efficiency of SACI using ion exchange conditions because of the polarization ionization mechanism of the buffer ion. [6,7] These results led us to develop a method for monitoring the enterotoxin A content in milk biological matrix by LC-CEC-SACI-MS/MS. Levels of enterotoxin A in milk vary depending on the presence of S. aureus and its storage conditions.…”
Section: Lc-rp-esi-ms/ms and Lc-rp-saci-ms/msmentioning
confidence: 99%